The Haredim as a challenge for the Jewish State: The culture war over Israel's identity - Peter Lintl (Stiftung Wissenschaft und Politik (SWP), 2020)
A culture war is being waged in Israel: over the identity of the state, its guiding principles, the relationship between religion and the state, and generally over the question of what it means to be Jewish in the "Jewish State". The Ultra-Orthodox community or Haredim are pitted against the rest of the Israeli population. The former has tripled in size from four to 12 percent of the total since 1980, and is projected to grow to over 20 percent by 2040. That projection has considerable consequences for the debate. The worldview of the Haredim is often diametrically opposed to that of the majority of the population. They accept only the Torah and religious laws (halakha) as the basis of Jewish life and Jewish identity, are critical of democratic principles, rely on hierarchical social structures with rabbis at the apex, and are largely a-Zionist. The Haredim nevertheless depend on the state and its institutions for safeguarding their lifeworld. Their (growing) 'community of learners' of Torah students, who are exempt from military service and refrain from paid work, has to be funded; and their education system (a central pillar of ultra-Orthodoxy) has to be protected from external interventions. These can only be achieved by participation in the democratic process. Haredi parties are therefore caught between withdrawal and influence. Whilst protecting their community, they try to both combat tendencies that run counter to their conception of Jewishness as 'defenders of the Jewish character of the state', and to gain more importance within state and society for principles of religious law. This impetus to shape affairs is recent. The Haredim are changing both state and society, and they in turn are changed by them. Responses from within the community to this fact range from calls for isolation to those for integration within the state to those for taking it over. For Israel's international partners, the Haredim's growing influence will necessarily mean more negotiation, especially where liberal and emancipatory issues are at stake.
Keywords: 320